Genotyping Cyclospora cayetanensis From Multiple Outbreak Clusters With An Emphasis on a Cluster Linked to Bagged Salad Mix—United States, 2020. (4th October 2021) - Barratt, Joel; Ahart, Lauren; Rice, Marion; Houghton, Katelyn; Richins, Travis; Cama, Vitaliano; Arrowood, Michael; Qvarnstrom, Yvonne; Straily, Anne
Abstract: Cyclosporiasis is a diarrheal illness caused by the foodborne parasite Cyclospora cayetanensis . Annually reported cases have been increasing in the United States prompting development of genotyping tools to aid cluster detection. A recently developed Cyclospora genotyping system based on 8 genetic markers was applied to clinical samples collected during the cyclosporiasis peak period of 2020, facilitating assessment of its epidemiologic utility. While the system performed well and helped inform epidemiologic investigations, inclusion of additional markers to improve cluster detection was supported. Consequently, investigations have commenced to identify additional markers to enhance performance. Abstract : A Cyclospora genotyping method developed at CDC was used to complement investigations of cyclosporiasis outbreaks in 2020. The tool detected clusters associated with the largest cyclosporiasis outbreak from 2020, among others. Opportunities for refinement of the tool were also highlighted.